Mechanical And Microstructural Assessment Of Synthetic Aluminosilicate Based Geopolymer Dental Material - Andrie Harmaji; Oqy Diadara Putri; Bambang Sunendar (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Orthodontic treatment with fixed brackets was performed to transmit the pressure from the wire to the periodontal tissues to produce tooth movement. Ceramic material can be used not only to improve the aestheticness but also maintains good mechanical properties. This study aims to determine the mechanical properties and morphological of synthetic aluminosilicate based geopolymer for aesthetic orthodontic brackets applications made by synthesizing alumina (Al2O3), silica (SiO2), and magnesia (MgO) from sol-gel method. Geopolymer nanocomposite was made by activating synthetic precursor with alkali solutions consists of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) solution which has molarity variations of 8M (GP-8M) and 14M (GP-14M). The test results using an X-Ray Diffractometer (XRD) showed that the crystalline phase of (Mg,Si)Al2O4 spinel was successfully presented in the synthesized nanocomposite. The average hardness test results using the Vickers hardness tester for Geopolymer Nanocomposite with 8M and 14M alkali activator were 259.15 and 298.90 VHN, respectively. The results of the surface morphological characterization using Scanning Electron Microscope (SEM) of the samples showed the porosity of GP-14M was smaller than GP-8M, which explains the hardness test value difference. This shows Geopolymer is a potential material for orthodontic brackets manufacture.